Food and Safe Water in Disasters - Sayılı, Uğurcan; Sak, Kevser; Sıddıkoğlu, Esin; Erginöz, Ethem (Cerrahpaşa Medical Journal, 2023)
Disasters, which are an important part of human history, make access to food and safe water difficult and affect human health. During a disaster or emergency, everyone must be provided with food and safe water for at least 3 days. These foods should be easily prepared, have high energy, prevent dehydration, and be durable, such as canned foods, cereals, legumes, nuts, dried fruits, and meats. After the acute period is over, food stores should be designed to meet the requirements adequately. For a total of 2100 kcal/day, at least 10% of the total energy should be from protein and at least 17% from fats. It is the most practicable and healthy option that is to meet the drinking water requirement with bottled water immediately after disasters and until temporary settlement is established. Mains, water should be brought to the area without delay, regardless of temporary or permanent settlement. If water cannot be supplied with bottled water and central chlorination, appropriate techniques such as filtration, chlorination, and boiling must be applied for unsafe water, especially until safe water is provided by aid organizations. These methods, which only remove physical and microbiological contamination in water, should be applied until a long-term solution is developed. Cite this article as: Sayılı U, Sak K, Sıddıkoğlu E, Erginöz E. Food and safe water in disasters. Cerrahpaşa Med J 2023;47(S1):17-22.